A clinical study to evaluate the effect of umami taste on the oral stereognostic ability of complete denture patients - Vinod Bandela; Shital Sonune; Kulashekar Reddy Nandalur; Eatedal Mukhlef Alruwaili; Alreem Abdulaziz Alnuman; Miad Abdulnasser Alahmed; Faisal Abdullah Eldosary; Lama Naif Alsayil; Faisal Nami Alsinani (Brazilian Dental Science)
Objective: This study aimed to assess the effect of umami taste on the oral stereognostic ability of patients with complete dentures. Material and Methods: Patients with complete dentures were recruited from a dental college and informed consent was obtained from all participants. The participants were randomly assigned to either the umami or control group. Their oral stereognostic ability was assessed using standardized test samples made from raw carrots presented in both plain and umami-flavored forms. Participants’ ability to identify shapes within the oral cavity was recorded, and statistical analyses were performed to compare oral stereognostic ability scores between the umami and control groups. Results: Participants exposed to umami taste stimuli demonstrated significantly higher mean scores for oral stereognostic ability compared to those in the control group. The umami group achieved a mean score of 8.3 (±1.5), whereas the control group had a slightly lower mean score of 6.7 (±1.2). This difference was consistent across all test shapes, indicating a potential enhancement in oral sensory function associated with umami taste perception. Male participants achieving higher mean scores than female participants in both the umami and control groups. Conclusion: This study provides evidence supporting the potential benefits of umami taste perception in enhancing the oral stereognostic ability of patients with complete dentures. Further research is warranted to elucidate the underlying mechanisms and explore the long-term outcomes, ultimately contributing to enhanced patient care in prosthodontics.